(untitled) (Education in the 21st Century, 2023)
This article reviews the main optical-graphical disorders of writing in visually impaired primary schoolers. It is known, that visual impairment significantly complicates the playing, physical, cognitive, educational, labour and other types of activities of children, their orientation in macro and micro spaces. Therefore, the role of vision in writing can hardly be overestimated. The visual control plays a very important role in observing graphical norms, rules and conditions of writing in the formation and development of visual skills of visually impaired 140 students. In this connection, the study of optical-graphical disorders in the writing of visually impaired primary schoolers will serve the basis for the development of special pedagogical approaches and terms of application for the organization and implementation of work aimed at the prevention and correction of graphical writing disorders of visually impaired primary schoolers. It is well known, that the formation and development of graphical skills of visually impaired students is to be started from the first grade, as it is more difficult to correct or eliminate opticalgraphical writing disorders in higher grades. Thus, the success of all the work depends on the informative level of primary school’s teachers about graphical writing disorders of their students, the means, methods and conditions of their use for carrying out the prevention and correction works. This defines the necessity to study optical-graphical writing disorders of visually impaired primary schoolers and to develop special pedagogical approaches and conditions for the prevention and correction of these disorders.